1999
DOI: 10.1016/s0029-7844(99)00305-1
|View full text |Cite
|
Sign up to set email alerts
|

Diet and uterine myomas

Abstract: Myoma is associated with beef and ham consumption, whereas high intake of green vegetables seems to have a protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 15 publications
6
80
2
1
Order By: Relevance
“…This observation is similar to other studies 14,15 .Increased BMI and tubal sterilisation were found to be risk factors in some studies. Our study do not show any association for these risk factors 8,16 .…”
Section: Discussioncontrasting
confidence: 90%
“…This observation is similar to other studies 14,15 .Increased BMI and tubal sterilisation were found to be risk factors in some studies. Our study do not show any association for these risk factors 8,16 .…”
Section: Discussioncontrasting
confidence: 90%
“…In a case-control study in Italy (Chiaffarino et al 1999), a moderate association was found between the risk of uterine myomas and the consumption of beef, other red meat, and ham, whereas a high intake of green vegetables seemed to have a protective effect. Unfortunately, no estimate of the total caloric intake was obtained, and no attempt was made to estimate the amount of fat in the diet for cases and controls, although one might assume that a higher intake of beef would be associated with a greater amount of fat in the diet.…”
Section: Dietmentioning
confidence: 96%
“…Despite the limitations of the study, the results are interesting and raise a number of issues. Because fibroids are known to be hormonally responsive tumors, are the dietary risks noted above (Chiaffarino et al 1999) secondary to the effects of various food groups upon the bioavailability of estrogen or progesterone? Is the protective effect of a high intake of green vegetables related to the fiber, some other undetermined component, such as a vitamin, or a corresponding reduction of fat in the diet?…”
Section: Dietmentioning
confidence: 99%
“…One study [31] has specifically addressed the question of dietary influences on the prevalence of fibroids. In an Italian population, 843 women with fibroids were compared with 1557 women without.…”
Section: Diet and Fibroidsmentioning
confidence: 99%